Acupuncture combined with metformin versus metformin alone to improve pregnancy rate in polycystic ovary syndrome: A systematic review and meta-analysis - Chen, Xin; Lan, Ying; Yang, Lijie; Liu, Yang; Li, Hongyu; Zhu, Xinyun; Zhao, Yuemeng; Long, Caiyi; Wang, Mengjing; Xie, Qingling; Li, Zhao; Wu, Jie (Frontiers in Endocrinology, 2022)
Objective: To evaluate the comparison between acupuncture and acupuncture combined with metformin in improving the pregnancy rate of people with polycystic ovary syndrome (PCOS). Methods: A literature search of eight databases resulted in nine Randomised controlled trials (RCTs) that assessed the effect of acupuncture combined with metformin on pregnancy rate in PCOS patients compared with metformin alone. Subsequently, data extraction and analysis were conducted to evaluate the quality and risk of bias of the methodological design of the study, and meta-analysis was conducted on the RCT data. Results: Nine RCTs, including a total of 1159 women, were included. Acupuncture can improve pregnancy rate.It was analyzed according to the diagnostic criteria of PCOS (Z=2.72,P=0.007, relative risk(RR) 1.31,95%CI 1.08 to 1.60,P=0.15, I2=41%). Analysis was performed according to different diagnostic criteria of pregnancy (Z=3.22,P=0.001,RR 1.35,95%CI 1.13 to 1.63,P=0.12,I2=42%).Acupuncture can improve ovulation rate. Subgroup analysis was performed according to the number of ovulation patients (Z=2.67,P=0.008,RR 1.31,95%CI1.07 to 1.59,P=0.04, I2=63%) and ovulation cycle (Z=3.57;P=0.0004,RR 1.18, 95%CI1.08 to 1.29, P=0.57, I2=0%). Statistical analysis also showed that acupuncture combined with metformin could improve homeostatic model assessment of insulin resistance (HOMA-IR)(mean difference(MD) -0.68, 95%CI-1.01 to -0.35, P=0.003, I2=83%). Conclusions: Based on the results of this study, compared with metformin alone, acupuncture combined with metformin has a positive effect on pregnancy rate, ovulation rate and insulin resistance in PCOS. However, due to the limitations regarding the number and quality of the included studies, the above conclusions need to be verified by further high-quality studies.